Solution! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The magic potion to keep animals away from small trees, as explained by the Food and Fertiliser Technology Centre in Spore 83, is indeed effective. Women running a tree nursery in northern Benin use the method successfully, dissolving fresh goat and...